Genetic variegation of clonal architecture and propagating cells in leukaemia - Anderson, Kristina; Lutz, Christoph; van Delft, Frederik W.; Bateman, Caroline M.; Guo, Yanping; Colman, Susan M.; Kempski, Helena; Moorman, Anthony V.; Titley, Ian; Swansbury, John; Kearney, Lyndal; Enver, Tariq; et al. (Nature (London), 2011)
Little is known of the genetic architecture of cancer at the subclonal and single-cell level or in the cells responsible for cancer clone maintenance and propagation. Here we have examined this issue in childhood acute lymphoblastic leukaemia in which the ETV6–RUNX1 gene fusion is an early or initiating genetic lesion followed by a modest number of recurrent or ‘driver’ copy number alterations. By multiplexing fluorescence in situ hybridization probes for these mutations, up to eight genetic abnormalities can be detected in single cells, a genetic signature of subclones identified and a composite picture of subclonal architecture and putative ancestral trees assembled. Subclones in acute lymphoblastic leukaemia have variegated genetics and complex, nonlinear or branching evolutionary histories. Copy number alterations are independently and reiteratively acquired in subclones of individual patients, and in no preferential order. Clonal architecture is dynamic and is subject to change in the lead-up to a diagnosis and in relapse. Leukaemia propagating cells, assayed by serial transplantation in NOD/SCID IL2Rγ null mice, are also genetically variegated, mirroring subclonal patterns, and vary in competitive regenerative capacity in vivo . These data have implications for cancer genomics and for the targeted therapy of cancer. Genetic variation in leukaemia cells Genome-wide analysis of cancer cells in individual patients has revealed extensive genetic heterogeneity. Two groups have now mapped genetic homogeneity in patients with acute lymphoblastic leukaemia (ALL). Mel Greaves and colleagues obtained mutational profiles of large numbers of single cells from 60 individuals with ETV6 – RUNX1 -positive ALL, while John Dick and colleagues profile BCR-ABL1 -positive ALL. Both groups deduce the evolutionary path by which different subclones emerge during disease progression. Leukaemia-propagating cells that transplant the disease mirror the genetic variegation of the bulk tumours, providing insight into the heterogeneity of these functional subpopulations at the genetic level. This work has implications for therapeutic approaches targeting the tumours and specifically leukaemia-propagating cells. Analysing single cells from human B-cell acute lymphoblastic leukaemias, this study maps the genetic heterogeneity of cells within a given tumour sample, the evolutionary path by which different subclones have emerged, and ongoing dynamic changes associated with relapse. Leukaemia-propagating cells that transplant the disease mirror the genetic variegation of the bulk tumours, providing insights into the heterogeneity of these functional subpopulations at the genetic level. This has implications for therapeutic approaches targeting the tumours and specifically leukaemia-propagating cells.